Contributions to the taxonomy of the Irano-Turanian genus Rhabdosciadium (Apiaceae): Nomenclatural notes, carpology, molecular phylogeny and the description of a new species from Bitlis (Turkey) - Firat, Mehmet; Güzel, Yelda (Phytotaxa, 2019)
A new Rhabdosciadium (Apiaceae) species, R. hizanense is described and illustrated from eastern Anatolia (Bitlis/Hizan). The new species has a distinct appearance with caespitose, low-growing habit and regularly pinnate, ovate-lobed leaves. It is most closely related to another recently described distinct Rhabdosciadium species, R. anatolyi, but differs from it by various features. Because R. anatolyi has been described based on a sample at the vegetative development stage, the holotype of the species has no flowers or fruits and the description of the species is incomplete. Hence, we designated a fully developed epitype for R. anatolyi. Comprehensive descriptions of both species are provided, including detailed photographs, geographical distribution maps, habitats and ecology, vernacular names, ethnobotanical usages, and IUCN conservation statuses. The phylogenetic position of the species within Rhabdosciadium, as well as within tribe Careae, was also studied based on nuclear-encoded ribosomal internal transcribed spacer region (ITS) sequence analysis.